Depression and a lack of socialization are associated with high levels of boredom during stroke rehabilitation: An exploratory study using a new conceptual framework. Issue 3 (16th March 2023) - Kenah, Katrina; Bernhardt, Julie; Spratt, Neil J.; Oldmeadow, Christopher; Janssen, Heidi
ABSTRACT: This exploratory sub-study aimed to develop a framework to conceptualize boredom in stroke survivors during inpatient rehabilitation, establish the effect of an activity promotion intervention on boredom, and to investigate factors that are associated with boredom. A framework was developed and explored within a cluster non-randomised controlled trial. Self-reported boredom was measured in 160 stroke survivors 13 (±5) days after rehabilitation admission; 91 participants received usual-care (control) and 69 had access to a patient-driven model of activity promotion (intervention). Individuals with pre-existing dementia or unable to participate in standard rehabilitation were excluded. Hierarchical logistic regression analysis was used to identify demographic, health and activity measures associated with boredom. Results indicated 39% of participants were highly bored. There was no statistically significant difference in boredom levels between treatment groups (difference −11%, 95% CI −26% to 4%). The presence of depression (OR 6.17, 95% CI 2.57–14.79) and lower levels of socialization (OR 0.96, 95% CI 0.92–0.99) predicted high boredom levels. This comprehensive framework provides a foundation for understanding the many interacting factors associated with boredom. Results suggest managing depression and improving opportunities for socialization may support meaningful engagement in rehabilitation to optimize recovery following stroke.